1999
DOI: 10.1021/la981038g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Arrangement in Two-Dimensional Streptavidin Crystals

Abstract: We studied the molecular arrangement of two-dimensional streptavidin crystals at the air-water interface over a range of pH values. We quantified the varying amounts of coexisting P1, P2, and C222 crystals in the different morphologies observed at pH 4.5-6.5. Chiral, needlelike crystals at pH 4.5 consist of P1 crystals with frequent line defects. Larger chiral domains near pH 5 are essentially all P1 coexisting with a small amount of P2, whereas at slightly higher pH values (near pH 5.5), H-shaped domains cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
108
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(120 citation statements)
references
References 31 publications
11
108
1
Order By: Relevance
“…One crystallographic axis (a-axis) is comprised of contiguous biotin-bound subunit pairs whereas the other axis (b-axis) is comprised of contiguous biotin-unbound subunit pairs. A previous study on the formation of streptavidine 2D crystal on supported planar lipid bilayers suggested that the interaction between biotin-unbound subunits is stronger than that between biotin-bound subunits [169], while another study suggested the reverse relationship [170]. Our analysis of the lattice defect movement Schematic of streptavidin arrays in C222 crystal.…”
Section: Lattice Defects In 2d Protein Crystalsmentioning
confidence: 57%
“…One crystallographic axis (a-axis) is comprised of contiguous biotin-bound subunit pairs whereas the other axis (b-axis) is comprised of contiguous biotin-unbound subunit pairs. A previous study on the formation of streptavidine 2D crystal on supported planar lipid bilayers suggested that the interaction between biotin-unbound subunits is stronger than that between biotin-bound subunits [169], while another study suggested the reverse relationship [170]. Our analysis of the lattice defect movement Schematic of streptavidin arrays in C222 crystal.…”
Section: Lattice Defects In 2d Protein Crystalsmentioning
confidence: 57%
“…On highly fluidic planar lipid layers containing a biotinylated lipid, streptavidin self-assembles into three distinct crystalline arrangements (types 1-3), depending on the crystallization conditions such as pH [28] and ionic strength [29]. The 2D crystals with each arrangement have P2 symmetry and the crystal forms remain unchanged for a long time (>12 h) on changing the buffer solution after crystallization.…”
Section: Streptavidin 2d Crystal Surfacementioning
confidence: 99%
“…To begin with, many pure organic materials and their aqueous solutions undergo dendritic crystallization when they are cooled below their liquidus temperatures. Typical examples are ammonium chloride [63], pivalic acid [64], cyclohexanol [62], succinonitrile [54], cholesterol [65], and protein streptavidin [66][67][68]. Under 'lagoon-like' conditions aqueous solutions of potassium cyanide and ammonium hydroxide yield heterogeneous cyanide polymer particles [69].…”
Section: Justificationmentioning
confidence: 99%